Integrated Marketing Communications and Factors of Confidence towards the Choice of Housing Loan Services with Gender Diversity - Torthienchai, Narudom (Journal of Management Science, Ubon Ratchathani University, 2024)
Cultural shifts have led to the legalization of same-sex marriage within the LGBTQ+ community. In Thailand, the legal system is working on addressing issues in various business sectors.This study examines the financial and health conditions of individuals of different genders in Thailand, focusing on "Integrated Marketing Communications and Factors of Confidence Towards the Choice of Housing Loan Services with Gender Diversity." The research aims to analyze factors influencing housing loan product selection among individuals of diverse genders. A mixed-method approach was employed. Qualitative research involved interviews with five marketers from major Thai banks offering housing loans and financial institution employees. Quantitative data was gathered via questionnaires from a sample of 400 individuals of diverse genders who applied for housing loans. Data analysis incorporated descriptive statistics, confirmatory factor analysis (CFA), and structural equation modeling (SEM). Findings revealed that integrated marketing messages and participant attitudes influenced trust in housing loan products. However, increased confidence did not significantly impact the decision to use these services. Instead, decisions were shaped by marketing communications offering favorable interest rates. Mortgage products were unaffected by attitudes identified as decision-making factors. LGBTQ+ individuals have access to equivalent loan terms as the general population through online and offline platforms. Bank representatives provide support to address loan inquiries, ensuring inclusivity. This study highlights the role of integrated marketing in fostering trust while emphasizing the importance of equitable financial services for all genders.